Smart Mail Management System at the Faculty of Science and Technology, Universitas Ibrahimy - Wardhatun Khasanah; Abd. Ghofur; Firman Santoso (G-Tech: Jurnal Teknologi Terapan, 2026)
The increasing demand for efficient administrative services in higher education institutions has highlighted the need for effective correspondence management systems. Conventional mail handling processes often result in delays, misrouted documents, difficulties in archiving, and challenges in information retrieval. This study aims to develop a web-based Smart Mail Management System by integrating Optical Character Recognition (OCR), rule-based intelligent routing, automated notifications, and digital approval features to improve correspondence management within the Faculty of Science and Technology, Universitas Ibrahimy. The research employed a Research and Development (R&D) approach using the Waterfall Software Development Life Cycle (SDLC), which consists of requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, documentation analysis, and literature review. OCR technology was utilized to convert scanned letters into digital text, while a rule-based mechanism automatically classified and routed correspondence to the appropriate recipient. The results indicate that the proposed system reduces manual processing, improves routing accuracy, accelerates document handling, enhances document traceability, and facilitates centralized digital archiving. Furthermore, the integration of automated notifications and digital approval features supports a more efficient administrative workflow. These findings demonstrate that the developed system contributes to improving the effectiveness, accuracy, and efficiency of correspondence management while supporting digital transformation initiatives in higher education institutions.